The Roman army and the New Testament - Zeichmann, Christopher B. (Lanham, Maryland Lexington Books/Fortress Academic, 2018)
A war machine in the Holy Land?. - Who were the soldiers in Palestine?. - What did the military do in early Roman Palestine?. - The military in the Gospels and Acts. - The military in the Pauline corpus. - The military in Revelation. - Reading a complicated Bible in complicated times
Literaturverzeichnis: Seite 145-163
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc -- Bible -- 30 B.C.-284 A.D; Armed Forces -- Foreign service; Military art and science in the Bible; Rome -- Army -- Foreign service -- Palestine; Rome -- History -- Empire, 30 B.C.-284 A.D -- Middle East -- Palestine -- Rome (Empire)